The Impact of XBRL Adoption on Audit Delay in the Financial and Non-Financial Industries in Indonesia - Saputro, B R W; Achjari, D (Program Studi Sistem Informasi, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2020)
Information technology implementation in the context of accounting, among others, is eXtensible Business Reporting Language (XBRL). This study aims to obtain empirical evidence of the impact of XBRL and type of industry on audit delay in Indonesia. Audit delay differences before and after XBRL implementation are also examined based on the types of financial and non-financial industries. The samples are 88 public companies obtained from Jakarta Stock Exchange. The collected data were analyzed using Generalized Least Square regression and Wilcoxon Signed Rank different test. The result fails to show the negative impact of the XBRL implementation on audit delay. This study finds that the type of industry associates with audit delay. However, there is no significant audit delay difference before and after the implementation of XBRL in the financial industry sector. As predicted, the non-financial industry sector shows a significant difference in audit delay before and after the implementation of XBRL. The contribution of the current study is the impact of XBRL implementation on audit delay in Indonesia is sensitive to the type of industry. Non-financial industry sector shows the impact of XBRL implementation on audit delay, while the financial industry sector does not.